Criminal Elements in Debt Restructuring During The Covid-19 Pandemic: Between Business Continuity and Legal Compliance - Hasanal Mulkan; Serlika Aprita (IHSA Institute, 2022)
The coronavirus (Covid-19) pandemic has hit the world economy, including Indonesia. In addition to direct handling of the epidemic problem, the government is also preparing to anticipate the impact of the economic slowdown caused by the pandemic. The government has issued regulations in relation to the forms of restructuring that can be carried out by banks and national financial institutions with their debtors that open up various alternative patterns of restructuring the settlement of obligations based on POJK No. 11 of 2020. This regulation has the potential to create an imbalance between creditors and debtors. The regulation provides the dominant flexibility for creditors to assess and offer forms of restructuring, so that there is the potential for an imbalance in the form of restructuring between creditors and debtors. The law enforcement scheme has its relevance to Law no. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK and PKPU). Some adjustments are needed so that the law which is intended to restore economic conditions by providing protection to creditors and debtors can find its context with the crisis caused by Covid-19. The results of this study indicate that PKPU is a strategic tool in designing debt restructuring. If the PKPU application is granted and peace is reached between the debtor and his creditors, the debtor concerned can continue his business activities. Some adjustments are needed so that the law which is intended to restore economic conditions by providing protection to creditors and debtors can find its context with the crisis caused by Covid-19. The results of this study indicate that PKPU is a strategic tool in designing debt restructuring. If the PKPU application is granted and peace is reached between the debtor and his creditors, the debtor concerned can continue his business activities. Some adjustments are needed so that the law which is intended to restore economic conditions by providing protection to creditors and debtors can find its context with the crisis caused by Covid-19. The results of this study indicate that PKPU is a strategic tool in designing debt restructuring. If the PKPU application is granted and peace is reached between the debtor and his creditors, the debtor concerned can continue his business activities.